MACROECONOMIC VARIABLES ANALYSIS (INFLATION AND BI 7-DAY REVERSE REPO RATE) ON SHARIA BANKING FINANCING IN INDONESIA - Haq, Furqonul; Fitrianto, Fitrianto; Yusfiarto, Rizaldi (Program Studi Ekonomi Islam FEI UNIDA Bogor, 2021)
ABSTRACTMacroeconomic variables are numerous, including inflation and interest rates determined by the central bank. The interest rate determined by Bank Indonesia is called the BI 7-Day (Reverse) Repo Rate. Inflation and BI 7-Day (Reverse) Repo Rate in the world of sharia banking in Indonesia are two important things that are always taken into account in carrying out the function of banks as a channel of financing to the public. It can be said that sharia banking financing directly or indirectly is greatly influenced by inflation and the BI 7-Day (Reverse) Repo Rate. To calculate the effect of inflation and BI 7-Day (Reverse) Repo Rate on sharia banking financing, this study was conducted. The data used in this study are inflation data, BI 7-Day (Reverse) Repo Rate and sharia banking financing on a monthly basis from 2010-2019 (120 months). The data is then processed by the statistic method using SPSS software with the t test and F test using. The independent variables used in this research are Inflation and BI 7-Day (Reverse) Repo Rate. Hypothesis testing shows that inflation has no significant effect on Islamic banking financing in Indonesia. Meanwhile, the BI 7-Day (Reverse) Repo Rate variable has a significant effect on Islamic banking financing in Indonesia. The results of the F test show that the inflation variable and the BI 7- Day (Reserve) Repo Rate simultaneously have an influence on Islamic banking financing in Indonesia.Keywords: Infation, BI 7-Day Reverse Repo Rate, Sharia Banking Financing